Exogenous selenium mitigates cadmium uptake and accumulation in two rice (Oryza sativa L.) varieties in cadmium-contaminated soil - Wenjiang Wu; Deqiang Qi; Yalong Chen; Jiaqi Wang; Ganggang Zhang; Qinghua Wang; Hongbin Niu; Quanzhi Zhao; Ting Peng (Scientific Reports, 2024)
Abstract Rice grown in cadmium (Cd)-contaminated soil, is a potential threat to human health, but exogenous selenium (Se) application on rice can mitigate Cd toxicity. However, the mechanisms underlying Se mitigation of Cd stress in ratoon rice (RR) are still poorly understood. We conducted a pot experiment with moderate Cd-contaminated yellow–brown paddy soil on two rice varieties ‘Taoyouxiangzhan’ (TX) and ‘Liangyou 6326’(LY). For all treatments, 1.0 mg kg−1 sodium selenite solution was added to soil. Treatment T1 was sodium selenite only, and in the other treatments 100 mg L−1 Se solution was sprayed on the leaves at seedling stage (T2), at tillering stage (T3), and in early anthesis stage (T4). Se treatments decreased Cd accumulation in rice grains and herbage. Under foliar spraying 100 mg L−1 Se at the seedling + 1.0 mg kg−1 Se in soil (T2), leaf Cd content decreased 16.95% in the current season and grains content decreased 46.67% in the subsequent season. Furthermore, grain Se content increased 0.94 mg kg−1 for the TX variety combined with the analysis of Cd bio-accumulation factor in grains, and Se treatments effectively decreased Cd grain concentrations due to reduced Cd translocation from roots to grains. TX variety rice showed a more pronounced response to Se treatments than LY.